A new norlignan lignanoside from Selaginella moellendorffii Hieron - Wei-sheng Feng; Ke-ke Li; Xiao-ke Zheng (Elsevier, 2011)
This study reports an investigation into the chemical constituents of the whole plant of Selaginella moellendorffii Hieron. Ten compounds, isolated and purified by column chromatography, were identified on the basis of spectral analysis and their physicochemical properties to be: (8R)-3,5-dimethoxy-4-hydroxyphenylpropylalcohol-8-(1-acetyl-3-methoxy-4-hydroxyphenyl)-9-O-β-d-glucopyranoside (moellenoside B) (1), amentoflavone (2), hinokiflavone (3), apigenin-7-O-β-neohesperidoside (4), apigenin-8-C-β-d-glucopyranoside (5), adenosine (6), uridine (7), 2,3,4,9-tetrahydro-1H-pyrido[3, 4-b]indole-3-carboxylic acid (8), vanillic acid (9), and lariciresinol (10). Compound 1 is a new norlignan lignanoside and compounds 4-10 were isolated from this plant for the first time.